EMPLOYEE ATTENDANCE INFORMATION SYSTEM AT BERKAH TRANSLATOR WEB-BASED - Mutqi Amrillah; Dwi Arif Wibowo; Revaldy Dwi Putra (Journal of Engineering, Electrical and Informatics, 2022)
In the modern environment, it is challenging to distinguish daily activities and employment from the usage of digital technology. This web-based employee attendance information system was designed to make it simpler for administrators and employees to keep track of attendance and recapitulation considering the importance and necessity of attendance for a business or institution. This information system has forms for employees to complete in order to view their attendance and notes, such as my attendance, add notes, and my notes. I developed this web-based information system with the assistance of php myadmin, notepad ++, dreamweaver, and visual studio. As a consequence of the research, an online employee attendance tracking system may boost company performance, particularly in the field of human resources.